To solve for the missing exponent in the equation
\[ \frac{h^{450}}{h^{?}} = h^{215}, \]
we can use the property of exponents that states
\[ \frac{a^m}{a^n} = a^{m-n}. \]
Applying this property, we can rewrite the left side of the equation:
\[ \frac{h^{450}}{h^{?}} = h^{450 - ?}. \]
Now we have the equation:
\[ h^{450 - ?} = h^{215}. \]
Since the bases are the same, we can equate the exponents:
\[ 450 - ? = 215. \]
To find the value of \( ? \), we can rearrange the equation:
\[ ? = 450 - 215. \]
Calculating this gives:
\[ ? = 235. \]
Thus, the missing exponent is
\[ \boxed{235}. \]